The stained-glass windows in the Entrance Hall of the Rijksmuseum : a coloured national art history - Leeuwen, Julia van (The Rijksmuseum bulletin, 2022)
Little attention has thus far been paid to the creation of the stained-glass windows in the Rijksmuseum’s Entrance Hall. However, a study of the pictorial programme for the windows reveals some remarkable choices. Driven by the ambition to present a broader overview of Dutch culture than had been disseminated until that time, the Catholic trio of Pierre Cuypers, Victor de Stuers and Joseph Alberdingk Thijm designed an iconographic programme for the stained-glass windows in the Entrance Hall. The programme for the stained-glass windows gives an overview of the major representatives of Dutch art history. Striking among them are two artists from the Northern Netherlands - Willem van Heerle and Jan van Terwen - who played almost no role in the Dutch art-historical canon at that time. The fact that these relatively unknown artists feature in the pictorial programme for the windows clearly indicates that the emphasis lies on the Roman Catholic Middle Ages and shows that it is a coloured version of Dutch art history.